The political economy of contract farming in china's agrarian transition - ZHANG, Qian Forrest (Institutional Knowledge at Singapore Management University, 2012)
How does rural China's political economy determine the motivations and constraints that drive small farmers and agribusiness companies into contract farming and shape its practice and impact? This paper identifies three distinctive features of contract farming in China – varied impact on rural inequality, unstable contractual relations and lack of competitiveness with other alternatives – and proposes tentative explanations linked to three features in rural China's political economy: strong collective institutions, active state support for agriculture and strong domestic markets. The recent turn in China's agrarian transition towards vertical integration of agriculture with industries is, however, undermining these conditions and may move China towards more convergence with other countries. Studying contract farming in China's unique political economy context shows not only how variations in the political economy can alter its practice and impact, but also how it needs to be evaluated in comparison with competing alternatives.